(untitled) (American Journal of Business Management, Economics and Banking, 2023)
The content and essence of the service sector in the article and the socio-economic significance of its rapid development, employment of the population in the service sectors an analysis of their structural structures is presented. A comparative analysis of certain data with the regions of Uzbekistan and Samarkand was made.